Soil respiration strongly offsets carbon uptake in Alaska and Northwest Canada. (4th August 2021) - Watts, Jennifer D; Natali, Susan M; Minions, Christina; Risk, Dave; Arndt, Kyle; Zona, Donatella; Euskirchen, Eugénie S; Rocha, Adrian V; Sonnentag, Oliver; Helbig, Manuel; Kalhori, Aram; Oechel, Walt; et al.
Abstract: Soil respiration (i.e. from soils and roots) provides one of the largest global fluxes of carbon dioxide (CO2 ) to the atmosphere and is likely to increase with warming, yet the magnitude of soil respiration from rapidly thawing Arctic-boreal regions is not well understood. To address this knowledge gap, we first compiled a new CO2 flux database for permafrost-affected tundra and boreal ecosystems in Alaska and Northwest Canada. We then used the CO2 database, multi-sensor satellite imagery, and random forest models to assess the regional magnitude of soil respiration. The flux database includes a new Soil Respiration Station network of chamber-based fluxes, and fluxes from eddy covariance towers. Our site-level data, spanning September 2016 to August 2017, revealed that the largest soil respiration emissions occurred during the summer (June–August) and that summer fluxes were higher in boreal sites (1.87 ± 0.67 g CO2 –C m −2 d −1 ) relative to tundra (0.94 ± 0.4 g CO2 –C m −2 d −1 ). We also observed considerable emissions (boreal: 0.24 ± 0.2 g CO2 –C m −2 d −1 ; tundra: 0.18 ± 0.16 g CO2 –C m −2 d −1 ) from soils during the winter (November–March) despite frozen surface conditions. Our model estimates indicated an annual region-wide loss from soil respiration of 591 ± 120 Tg CO2 –C during the 2016–2017 period. Summer months contributed to 58% of the regional soil respiration, winter months contributed to 15%, and the shoulder months contributed to 27%. In total, soil respiration offset 54% of annual gross primary productivity (GPP) across the study domain. We also found that in tundra environments, transitional tundra/boreal ecotones, and in landscapes recently affected by fire, soil respiration often exceeded GPP, resulting in a net annual source of CO2 to the atmosphere. As this region continues to warm, soil respiration may increasingly offset GPP, further amplifying global climate change.